Integrated Quality Management in Improving Customer Satisfaction - Nafi'atul Hasanah; Ahmad Qolfathiriyus Firdaus; Akhyak; Nur Efendi; Himad Ali (JMPI: Jurnal Manajemen, Pendidikan dan Pemikiran Islam, 2025)
This study aims to examine the implementation of Integrated Quality Management (Total Quality Management/TQM) in improving customer satisfaction at two madrasahs, namely MAN 2 and MAN 3 Tulungagung. The research focuses on three main aspects: policies, culture, and commitment in quality management implemented to meet the expectations of internal customers (teachers, staff, and students) as well as external customers (parents, the community, and other stakeholders). The research approach used is qualitative with a multisite study design. Data collection techniques are conducted through in-depth interviews, participatory observation, and document studies, while data analysis is performed through single case analysis and cross-site comparative analysis. The results of the study show that (1) the madrasah's quality policy based on Islamic values plays a crucial role in shaping the quality culture, (2) the formation of quality culture is carried out through agreements on fundamental values unique to each madrasah, and (3) the commitment of all madrasah personnel to quality implementation is greatly determined by the internalization of these values. This study emphasizes the importance of integrating policies, culture, and commitment in integrated quality management to achieve customer satisfaction in Islamic education environments.